"Perjalanan Jiwa Menuju Allah" Gagasan Agustinus Sebagai Titik Pendamai - Agustinus Purnama (Jurnal Orientasi Baru, 2007)
St. Augustine of Hippo was a restless seeker of truth. Never during more than seventy years of his life was there a period of quiet and security. This kind of life influenced greatly his way of thinking and finally his writings in philosophy and theology. Indeed, almost all his writings were polemical and controversial. In particular, his teaching on "the journey of soul toward God" was a great intellectual achievement in the history of theology as well as philosopy. His own restless soul came into maturity through that teaching, and eventually became a priviledged point of reference.